DNA repair gene XPD Asp312Asn and XRCC4 G-1394T polymorphisms and the risk of autism spectrum disorder - Dasdemir, S; Guven, M; Pekkoc, K C; Ulucan, H; Dogangun, B; Kirtas, E; Kadak, M T; Kucur, M; Seven, M (Cellular and Molecular Biology, 2016)
Autism spectrum disorder (ASD) is a complex disorder, and its extreme heterogeneity further complicates our understanding of its biology. Epidemiological evidence from family and twin studies supports a strong genetic component in ASD etiology. Oxidative stress and abnormal DNA methylation have been implicated in the pathophysiology of ASD. Brain tissues from ASD cases showed higher levels of oxidative stress biomarkers than healthy controls in postmortem analysis. Association between oxidative stress and DNA damage has been well-known. Thus, we sought to investigate a potential link between DNA repair genes and ASD and analyze the role of XPD Asp312Asn and XRCC4 G-1394T gene polymorphisms for ASD in the Turkish population. Genotyping was conducted by PCR-RFLP based on 100 patients and 96 unrelated healthy controls. We, for the first time, demonstrated a positive association between XRCC4 gene variants and ASD risk. Frequencies of XRCC4-1394 T/G+G/G genotypes were higher in patients (%34) than the controls (%18.7). The statistical analysis revealed that the individuals who had XRCC4-1394 T/G+G/G genotype had an increased risk for ASD (OR = 2.23, 95% CI = 1.10-4.55). However, no significant association was found for XPD Asp312Asn polymorphism with the risk of ASD. Our findings suggest that XRCC4 G-1394T polymorphism might be associated with ASD pathogenesis.